Evaluasi Efisiensi Alat Gali-Muat Terhadap Produktivitas Setelah Delay Shift Change pada Pembongkaran Overburden Bulan Februari 2019 di Pit AB RTS (Roto South) Tambang Batubara PT. Bukit Makmur Mandiri Utama Jobsite PT. Kideco Jaya Agung - Natasha Nur Ananda; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Overburden removal production at PT. Bukit Makmur Mandiri Utama jobsite PT. Kideco Jaya Agung uses large excavators that is Caterpillar 6020B and Komatsu PC2000. The average actual productivity at 07:00 - 08:00 a.m. on February 2019 at Pit AB RTS (Roto South) for one Caterpillar 6020B is 777 bcm/hour has not reached the target of 793 bcm/hour and five Komatsu PC2000 is 647 bcm/hour has not reached the target of 662 bcm/hour. Failure to achieve productivity targets due to obstacles after delay shift change. The excavators studied were Komatsu PC2000-07, PC2000-21, and PC2000-25 which had the most productivity not achieved. Standby hours affect work efficiency based on the theoretical formula of excavator productivity. Efforts are made to improve the work efficiency of excavators by looking at the root problems in the fishbone diagram and analyzing them so that they can be improvised solutions in increasing work efficiency. Factor of humans and methods is the most dominant factor causing productivity at 07:00 - 08:00 a.m. is not achieved. The amount of time is ineffective due to personal activities by the operator and the absence of control from the supervisor over the regulation of the number of haulers after delay shift change.